Direct injection of 188Re-microspheres in the treatment of hepatocellular carcinoma - Lin, Y.-Ch.; Tsai, S.-Ch.; Hung, G.-U.; Lee, J.-Ch.; Huang, Y.-S.; Lin, W.-Y. (Nuklearmedizin - NuclearMedicine, 2005)
The aim of this study was to compare the therapeutic efficacies of direct intratumoural injection of 188Re microspheres (DIRM) and direct intratumoural injection of ethanol (DIE) in rabbits bearing liver tumours. Materials and methods: Fifteen rabbits bearing liver tumours were divided into three groups: group 1 received DIE, group 2 received DIRM, and group 3 (control) received saline. Tumour size was measured by liver sonography before injection, as well as 2, 4, 8, and 12 weeks after injection. Survival time was calculated from the day of treatment to three months after treatment by Kaplan-Meier survival analysis. Results: The mean survival time was 68 ± 9.8 days for the rabbits in the DIRM group, 55.8 ± 11.8 days for the DIE group, and 38.8 ± 6.2 days for the control group. Conclusion: The rabbits survived longer in the DIRM group than in the DIE group although there is no statistical significance. We believe the DIRM method has a good potential to be an alternative to DIE for the treatment of liver tumours.
Keywords: Hepatocellular carcinoma; 188Re microspheres; ethanol injection